Blade shape optimization and internal-flow characteristics of the backward non-volute centrifugal fan. (June 2022) - Zhang, Hongjie; Wang, Zhengdao; Yang, Hui; Zhu, Zuchao; Wei, Yikun
The work proposed the double parameter optimization method of the non-volute centrifugal fan's blade profile based on the steepest descent method. Total-pressure efficiency improvement at the high-flow area was taken as an optimization objective. A method of applying the steepest descent method to modify the blade profile of backward centrifugal fan is proposed in this paper. The gradient descent direction was analyzed to design the blade profile and obtain the optimal blade profile at a high-flow rate. Besides, numerical simulations were carried out to analyze the aerodynamic performance and the internal flow characteristics of the centrifugal fan by the computational fluid dynamics method. Numerical results showed that the blade profile along the gradient descent was optimized to effectively increase the total pressure and the total pressure efficiency of the original model at the high-flow rate. The steepest descent method for local optimization could improve the fan blade design.